Gone to Pitchipoi A Boy's Desperate Fight for Survival in Wartime - Katz, Rubin (Jews of Poland, 2012)
In Gone to Pitchipoi Katz vividly recalls his experience growing up in the turmoil of WWII, and his extraordinary escape from the constant threats of Nazi occupied Poland. Born in 1931 in the picturesque countryside of Ostrowiec Świętokrzyskie, wherein more than a third of the population was Jewish, Katz experienced a constant juxtaposition of traditional ways of life with the tragedies of those years. Deemed unfit for labor camps, Katz was marked for certain death and forced to live on the run in a daily quest for food, shelter, and friendship. He eventually reunited with his sister, Fela, together encountering a series of narrow escapes and forging on to see the day of liberation. This book is a major contribution to our understanding of the fate of Jews in small Polish towns during the Second World War.